Investigation of Au and Ag segregation on Fe(001) with soft X-ray absorption - Bonell, F.; Lam, D.D.; Yoshida, S.; Takahashi, Y.T.; Shiota, Y.; Miwa, S.; Nakamura, T.; Suzuki, Y. (Surface science, 2013)
We investigated the X-ray absorption at the Fe L3 edge of Fe grown on Cr(001), Au(001) and Ag(001). Systematic variations in the absorption were observed depending on the nature of the buffer. They are explained by segregation of Au and Ag during Fe deposition at room temperature. By measuring wedge shaped samples, the segregated amounts could be measured. Taking into account the possible influence of roughness, we find that the segregated amounts of Au and Ag on a 1nm-thick Fe film are 0.8±0.3ML and 2.0±0.3ML, respectively. •Room temperature epitaxy of Fe on Cr(001), Au(001) and Ag(001).•Measurement of Fe L3 x-ray absorption with electron yield detection.•The measured electron yield reflects Au and Ag segregation on top of Fe.•Measurement of the electron escape depth through Au and Ag.•Estimation of the segregated amounts, taking into account the effect of roughness.